The influence of Brand Identification, Self-Expressiveness, and Experience on Repurchase Intention among Consumers of Beauty Clinic Services in Batam - Yulianto Putra, Edy; Gamelia, Warni; Hefri Ariyanto, Hepy (Jurnal Manajemen, 2025)
This study aims to analyze and identify the factors influencing re-peat purchase intention in beauty clinic services in Batam. Data for the study were collected through questionnaires distributed to 444 consumers who have experienced beauty clinic services in Batam. The analysis method applied was Structural Equation Modeling - Partial Least Squares (SEM-PLS), which was used to test the validity and reliability of the data and to evaluate the relationships between variables. Demographic data were processed using Statistical Program for Social Science (SPSS). The results of the study indicate varying influences between the variables exam-ined in the beauty clinic services in Batam. Brand identification was found not to have a significant effect on brand love. In contrast, brand love had a significant influence on satisfaction. The experience gained by consumers also had a significant effect on brand love. Furthermore, the satisfaction experienced by consumers positively and significantly influenced repurchase intention. Self-expressiveness also showed a significant influence on brand love. This research reveals that brand love plays a crucial role as a mediator in the relationship with repurchase intention. The findings also suggest that beauty clinics in Batam should focus on de-veloping brand love and positive experiences for consumers. The implications of this study recommend that beauty clinics in Batam prioritize strengthening brand identification and enhancing customer experience in order to increase satisfaction and customer loyalty. This research provides valuable insights for marketing strategies and service development in the beauty industry in Batam.